Compensation of hand-arm vibration syndrome in Canada - Thompson, Aaron; Turcot, Alice; Youakim, Sami; House, Ron (Canadian Acoustics, 2011)
A summary of the current compensation experience for HAVS in Canada, is provided by reviewing and comparing workers' compensation board policies, adjudication procedures, and recent claims data for HAVS in Canada's ten provinces and three territories. The Compensation Boards in each province and territory were contacted to request the criteria used for the adjudication of HAVS claims in their jurisdiction. The initial entitlement criteria used for HAVS claims varies widely by province/territory. The study found the number of accepted HAVS claims in Canada to be low, compared to prevalence estimates in other comparable industrialized countries. Significant variation in the compensation experience for HAVS across the Canadian provinces and territories is reported, calling for refinement of the entitlement criteria, case definition and assessment procedures used for the adjudication of HAVS compensation claims in Canada.